WELTKRIEGSPHILOSOPHIE AND SCHELER'S PHILOSOPHICAL ANTHROPOLOGY - V. Y. Popov; E. V. Popova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The research is aimed at understanding the philosophical and journalistic heritage of M. Scheler during 1914-1919. "The philosophy of war" is regarded as the middle link between the phenomenological and anthropological stages of its philosophical evolution. The theoretical and methodological basis of the study is the philosophical legacy of Max Scheler, as well as the work of domestic and Western researchers devoted to this issue. Problems of Weltkriegsphilosophie become comprehensible based on the historical, logical and comparative principles of historical and philosophical analysis, which allowed to theoretically reconstruct the cultural and historical context, philosophical sources and ideological intentions of the German philosopher. Originality. For the first time in domestic historical and philosophical thought, it proved that the works by Max Scheler of the First World War played an outstanding role in the formation of philosophical anthropology as a separate philosophical trend. Conclusions. The basis of the Weltkriegsphilosophie by Max Scheler is the philosophical comprehension of the war in which the thinker tries to see the high sacral meaning, where the sacrifices that the nation brings to the altar of victory are not in vain: the nation is rallying this sacrifice, its readiness for it. According to Scheler, war is the most effective means of forming the so-called "love communities", to which he refers combat brotherhood, family and nation as a "collective personality", which recognizes itself through war. The philosopher is disappointed to some part with militaristic enthusiasm in his later military journalistic works and calls for a spiritual and moral renewal of Europe, fed from Christian roots. At the heart of this renewal should be the principle of personal solidarity, based on the Christian idea of love. However, Catholic universalism is an insufficient means for the formation of a "love community" and a new man who is co-creator of God that constitutes the main core of the philosophical anthropology of Max Scheler, which emerges in the 20s of the twentieth century. Based on this, the article affirms the existence in Sheler’s works of an intermediate stage between his phenomenology and philosophical anthropology – Weltkriegsphilosophie (philosophy of the World War).